Designed Negative Feedback from Transiently Formed Catalytic Nanostructures. Issue 44 (20th September 2019) - Afrose, Syed Pavel; Bal, Subhajit; Chatterjee, Ayan; Das, Krishnendu; Das, Dibyendu
Abstract: Highly dynamic and complex systems of microtubules undergo a substrate‐induced change of conformation that leads to polymerization. Owing to the augmented catalytic potential at the polymerized state, rapid hydrolysis of the substrate is observed, leading to catastrophe, thus realizing the out‐of‐equilibrium state. A simple synthetic mimic of these dynamic natural systems is presented, where similar substrate induced conformational change is observed and a transient helical morphology is accessed. Further, augmented catalytic potential of these helical nanostructures leads to rapid hydrolysis of the substrate providing negative feedback on the stability of the nanostructures and realization of an out‐of‐equilibrium state. This simple system, made from amino acid functionalized lipids, demonstrates a substrate‐induced self‐assembled state, where the fuel‐to‐waste conversion leads to the temporal presence of helical nanostructures. Abstract : Burst catalysis : A substrate‐induced transient helical morphology was accessed as a self‐assembled state. Critically, burst hydrolytic rates of substrates result in disassembly, thus mimicking the dynamic instability of microtubules.